Regulation of cerebral metabolism during cortical spreading depression. Issue 11 (November 2016) - Feuerstein, Delphine; Backes, Heiko; Gramer, Markus; Takagaki, Masatoshi; Gabel, Paula; Kumagai, Tetsuya; Graf, Rudolf
We analyzed the metabolic response to cortical spreading depression that drastically increases local energy demand to restore ion homeostasis. During single and multiple cortical spreading depressions in the rat cortex, we simultaneously monitored extracellular levels of glucose and lactate using rapid sampling microdialysis and glucose influx using 18 F-fluorodeoxyglucose positron emission tomography while tracking cortical spreading depression using laser speckle imaging. Combining the acquired data with steady-state requirements we developed a mass-conserving compartment model including neurons and glia that was consistent with the observed data. In summary, our findings are: (1) Early breakdown of glial glycogen provides a major source of energy during increased energy demand and leaves 80% of blood-borne glucose to neurons. (2) Lactate is used solely by neurons and only if extracellular lactate levels are >80% above normal. (3) Although the ratio of oxygen and glucose consumption transiently reaches levels <3, the major part (>90%) of the overall energy supply is from oxidative metabolism. (4) During cortical spreading depression, brain release of lactate exceeds its consumption suggesting that lactate is only a circumstantial energy substrate. Our findings provide a general scenario for the metabolic response to increased cerebral energy demand.